Measuring Corporate Resilience Using Dynamic Factor Analysis: Evidence from Listed Companies in China - Chunguang Sheng; Jingyan Li (Systems, 2025)
The scientific measurement of corporate resilience is a prerequisite for identifying risk vulnerabilities, formulating targeted support policies, and enhancing the stability of the economic system. This paper utilizes data from 2054 listed companies on China’s A-share market from 2007 to 2023 to construct a corporate resilience evaluation system integrating three dimensions: risk resistance, adaptive adjustment, and recovery growth. Using a multi-level dynamic factor analysis, it depicts the multi-dimensional structure of resilience while introducing time series dynamic changes. This study found that corporate resilience has shown a steady upward trend overall, with phased fluctuations before and after major crisis events, which is highly consistent with macro- and microeconomic indicators. And fluctuations are primarily concentrated among low-resilience enterprises. The further analysis of low-resilience enterprises revealed the following: At the industrial level, compared with the primary industry, the secondary and tertiary industries have a higher proportion of low-resilience enterprises. At the regional level, the proportion of low-resilience enterprises in eastern and central regions decreased during shocks, while western regions showed a significant divergence, and northeastern regions consistently underperformed. This study offers empirical evidence and management insights for strengthening corporate resilience and enhancing the resilience of China’s economy. It also offers valuable insights for other countries in addressing external uncertainties and building economic resilience.